Sistem Pertanian Terpadu Hedgerow Meningkatkan Pendapatan Petani Lahan Kering - Risal, Darmawan (Jurnal Ecosolum, 2018)
Agricultural systems carried out by local farmers on dry land sloping topography Gowa in particular proved a negative impact on production which impact on decreasing the income of farmers. This study aims to determine whether the Hedgerow integrated farming systems may increase the income of dryland farmers. The research was conducted on dry land with a slope of 30% in Gowa. Research using randomized complete block design with four treatments and two replications. Components of each treatment that is P0 (corn, mangosteen, Gliricidia), P1 (corn, mangosteen, Gamal, mischantus), P2 (corn, mangosteen, Gamal, Setaria), P3 (corn, mangosteen, Gamal, elephant grass) economic analysis using nalisis production, R / c Ratio and NPV. The results of the analysis of production per season showed P3 treatment is treated with the highest income of USD 19,123,446 and in line with the highest total receipts per year. R / c ratio integrated farming systems Hedgerow very feasible where P3 has feasibility level high while the NPV P0 is treated with NPV room where the first year until the 6th year that are in deficit figures while P1, P2, P3 obtained an increase from the first year until the 20th year. This study proves that integrated farming systems Hedgerow increase farmers' income and very worthy to be applied on dry land marginal bertopografi particularly skewed